Users' mouse/cursor movements in two web-based library catalogue interfaces. - Chee, Dexter Siang Lin. (2008)
Screen-capture files of 40 subjects interacting with two university Web-based library catalogue interfaces are analysed to identify basic mouse/cursor movements that indicate usability issues. The possible explanations of the behaviour are described from cognitive and mental model perspectives. This study seeks to observe the mouse/cursor movements and find out the cognitive reasons for such behaviours.